MAXILLARY INFLAMMATORY MYOFIBROBLASTIC TUMOR - Rao, Deeksha P; Pujary, Kailesh; Mathew, Mary; Bhandarkar, Ajay M (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Inflammatory myofibroblastic tumor (IMT) is a benign disorder of locally aggressive nature. It is an indolent tumor with a slowly progressive course and varied manifestation presenting with a wide range of clinical manifestations depending on the site of origin. We present a case of IMT in the maxillary sinus presenting with hemifacial pain, oculomotor palsy and ptosis which was successfully treated with endoscopic local excision and oral steroid therapy. Keywords: Plasma cell granuloma, Maxillary pseudotumor, Maxillectomy, Steroid therapy, Radiotherapy.